(3JMaI GdeQjO debOeI GdJLhjOs - (3eLghds ((3eMeO Hf eMeO Hf jhSa GdNGdOjs)
(3ChdgG (B:s
(3HYO GdHSedI hGdGSJYGfI ; GdMeO ddg eLhO GdCTjGA HEJbGf GdPj ejR Hjf GdEfSGf hGdMjhGf hHYO aEf aVjdI GdYde fYeI XGgQI heJdHShgG HOhQ RGgQI hGNJGQ Gddg WGFaI GQJVGgG dMaX cJGHg GdcQje hdeG cGfJ GdebOeI GdLRQjI aj GdJLhjO ef MSf HgLJgG hJgPjH CdaGXgG aGSJNQJ Gddg JYGdi hhVYJ YdjgG TQMG SejJg JMaI GdeQjO debOeI GdJLhjOs
(3BNQgG (B:s
(3hGdMeO ddg dgG NJGe (B= (3Ke GdUdGI HYO hGdSdGe deG aQZ GfJgi ZQVg ef gPG GdfXe hgh GTJeGdg Ydi CYXe GdegeG NJe HeG GaJJM ef MeO Gddg hCfG GJVQY Edi GddY JYGdi aj Cf jLYdg YedG eHQhQG hSYjG eTchQG hCf jef Ydj HGdNdGU hEf YOe UOb GdENdGU hCf jfaY Hg cd WGdH hQGZH Je TQM GdLRQjI GdeSei HJMaI GdeQjO debOeI GdJLhjOs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdbQGAGJ hGdJLhjOs